Comparing serum microRNA levels of acute herpes zoster patients with those of postherpetic neuralgia patients. Issue 8 (February 2017) - Huang, Ying; Li, Xihan; Tao, Gaojian; Zhu, Tong; Lin, Jian
Abstract : Abstract: Postherpetic neuralgia (PHN) is commonly defined as pain persisting for at least 3 months after acute herpes zoster (AHZ) rash presentation. About one-tenth of all acute herpes zoster patients develop PHN. Circulating microRNAs (miRNAs) are promising biomarkers for infectious diseases; however, there has been no relationship established between circulating miRNAs and PHN to date; the aim of the present investigation was to elucidate this relationship. We compared serum levels of miRNA in PHN and AHZ patients. Twenty-nine patients with PHN and 37 patients with AHZ participated. MiRNA serum levels were determined via TaqMan Low Density Array (TLDA) and confirmed individually by RT-qPCR. TLDA results showed that the expression levels of 157 serum miRNAs in PHN patients were distinct from those in AHZ patients. Among these PHN patient serum miRNAs, 17 were upregulated and 139 were downregulated in contrast to those in AHZ patients. Receiver operational characteristic (ROC) curve analysis and RT-qPCR results altogether confirmed that the levels of miR-34c-5p, miR-107, miR-892b, miR-486–3p, and miR-127–5p were notably increased in PHN patients in comparison with those of AHZ patients. These miRNAs in circulation may regulate numerous relevant pathways. A few likely participate in the nervous system and inflammatory reactions. This study is the first to show that the expression profiles of numerous miRNAs vary in the PHN process. Among these, 5 types of serum miRNAs are very likely related to PHN development. Abstract : Supplemental Digital Content is available in the text